Analysis of The Effects of Training, Motivation, Work Environment, Leadership And Compensation on Employee Performance In Generation Z In Batam City - Sentoso, Antony; Setiawan, Agustinus; Vivianti, Weni (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
Amid the company's rapid growth, various new issues continue to emerge. Therefore, the performance and potential of employees must be maximized by the business. A company's success is a direct result of the people who work there. The research aimed to determine how Generation Z employees in Batam performed in leadership, training, motivation, work environment and weaknesses. This research uses various methods to test hypotheses regarding variables that may influence the performance of Generation Z employees in Batam City. Quantitative research methods were used on 385 respondents as research samples. The collected data was checked for outliers, evaluated for data validity and reliability, checked for traditional premises (normality, multicollinearity, and heteroscedasticity), and fit for hypotheses. In Batam City, Generation Z, leadership and wage variables significantly boost employee performance, while training, motivation and work environment factors do not match the results of the hypothesis analysis